1975
DOI: 10.1039/dt9750001207
|View full text |Cite
|
Sign up to set email alerts
|

Bonding studies of compounds of boron and the Group 3–5 elements. Part XIII. He(I) photoelectron spectra of phosphines RnPX3–n(R = Me or But; X = H, Cl, or F; n= 1–3), (Me2N)nPCl3–n(n= 1–3), and (R2N)PF2(R = Me or Et)

Abstract: The He(!) photoelectron spectra of the title compounds have been measured. An empirical assignment of most of the bands is proposed and the effects of various substituents on the phosphorus lone-pair ionisation potentials are assessed. Correlations are made with various other parameters relating to phosphine basicity, and it is concluded that the phosphorus lone-pair i.p. provides a reasonable measure of relative basicity or 6donor ability within related series of compounds.of Sussex, Brighton BN1 9QJ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 1 publication
(1 reference statement)
1
22
0
Order By: Relevance
“…Weiner and Lattman (25) found a good correlation between lone pair IP and o , but point out that this implies that there are no major changes in hybridisation at phosphorus through the series. Another study (26) corroborates this by showing that while there may be good correlations within a series of closely related phosphines, it is not a good technique for determining the relative basicities of very different phosphines such as PCI, and (P (C6-H,),. Indeed, while the IP of all the triarylphosphines used in this study correlate well with p& (Fig.…”
Section: Results and Discussion (A) Basicities Of Phosphinesmentioning
confidence: 57%
See 1 more Smart Citation
“…Weiner and Lattman (25) found a good correlation between lone pair IP and o , but point out that this implies that there are no major changes in hybridisation at phosphorus through the series. Another study (26) corroborates this by showing that while there may be good correlations within a series of closely related phosphines, it is not a good technique for determining the relative basicities of very different phosphines such as PCI, and (P (C6-H,),. Indeed, while the IP of all the triarylphosphines used in this study correlate well with p& (Fig.…”
Section: Results and Discussion (A) Basicities Of Phosphinesmentioning
confidence: 57%
“…3), the point for P(t-C,H,), is far from the line. The C-P-C angle in the triarylphosphines is probably close to the 103.0" of P(C6H,), (27) while the angle in P(t-C4H,), is larger at 10Y (26,28 …”
Section: Results and Discussion (A) Basicities Of Phosphinesmentioning
confidence: 99%
“…X‐ray (XPS) and ultraviolet (UPS) photoelectron spectroscopy is widely applied to the measurement of the core‐electron binding energies ( E ) and vertical ionization potentials ( I ) for gaseous nitrogenated1–13 as well as organophosphorus1, 2, 6, 14–23 compounds. Photoelectron spectroscopy is based on the use of a gas‐phase ionization process initiated by photons with the energy h ν: where R C BX n is a neutral molecule, R C•+BX n is a radical cation, and e − is an electron 2, 3.…”
Section: Introductionmentioning
confidence: 99%
“…In phosphorous chemistry, photoelectron spectroscopy (UV-PES) has been used to characterise the valence electronic structure of neutral phosphine ligands. [43][44][45][46] It has been shown that the lower the first (lone pair) ionisation energy of phosphine ligands, the better they are as donors in a coordinative bond. Photoelectron spectroscopy is thus one of the few physical measurements that can assess-at least in a qualitative sense-the electronic properties and behaviour of ligands in the absence of metals.…”
Section: Introductionmentioning
confidence: 99%